Therapeutic modality of the long QT syndrome: Lesson from the past - Edin Begic; Enisa Hodzic; Zijo Begic; Amer Iglica; Nedim Begic; Omer Jusic (Research in Cardiovascular Medicine, 2020)
Long QT syndrome (LQTS) is a rare (1:2500–1:10,000) inherited disorder characterized by the onset of arrhythmogenic syncope, polymorphic ventricular tachycardia, and sudden cardiac death. The aim of this article was to describe an unexpected success with an unusual therapeutic modality of a patient diagnosed with LQTS syndrome (suspected Romano–Ward syndrome) during an 8-year period. A 59-year-old female patient was admitted to the hospital due to chest pain and nausea, and after diagnostic and therapeutical approach, a permanent dual-chamber rate-modulated (DDDR) pacemaker was implanted instead of the implantable cardioverter defibrillator (ICD). During the 8-year period, the patient remained stable, without rhythm disorder. Romano–Ward syndrome as a congenital LQTS carries a high risk of sudden cardiac death and presents an indication for ICD. In this patient, for objective reasons, this could not be performed. Implantation of a DDDR with an appropriate pharmacological therapy, including propranolol, in this case, proved to be a successful therapeutic modality.